The role of the shape resonance state in low energy electron induced single strand break in 2′-deoxycytidine-5′-monophosphate1. Issue 23 (21st June 2015) - Bhaskaran, Renjith; Sarma, Manabendra
<x xml:space="preserve">Abstract</x> Low energy electron (LEE) induced single strand break (SSB) has been studied for 2′-deoxycytidine-5′-monophosphate (5′-dCMPH) molecules in the gas phase by means of ab initio electronic structure methods and local complex potential based time-dependent wavepacket quantum mechanical calculations.